Western Images of Meccan Pilgrims in the Dutch East Indies, 1800-1900 - Syed Muhd Khairudin Aljunied, (Universiti Kebangsaan Malaysia, 2005)
This paper examines Western images of returned Meccan pilgrims (hajjis) in the nineteenth century Dutch East Indies. I argue that the persistent presence of various Western literary works that promoted stereotypical images of the hajjis in the 19th century reflects a dominant discourse, which asserted that the version of Islam that the Arabs had practised and preached was inevitably dangerous and should be contained. With the advent of direct imperialism in the second half of the nineteenth century, such a discourse became established as “natural truths” that had to large extent subsumed alternative viewpoints, which sought to amend it. Hence, by the turn of the century, hajjis, as a force, were essentialised as a negative influence in the Dutch East Indies